The impact of early tracheostomy toward the functional outcome of severe head injury patients - Mahmud, Muhammad Farhan; Mohamed Ludin, Salizar; Awang, Mohamed Saufi (2023)
Introduction: Patients with severe head injury (SHI) may require mechanical ventilation support for cerebral protection. However, they are at risk of experiencing a prolonged mechanical ventilation episode which requires them for the initiation of tracheostomy. In addition, this vulnerable group also are at risk of having a poor prognosis and functional outcome due to severely impaired cognitive function. The past study documented the functional outcome status of SHI patients. However, the impact of early tracheostomy was not properly documented, especially in the Malaysian setting. Purpose: The objective of this study is to determine the impact of early tracheostomy toward the functional outcome of SHI patients. Methodology: A retrospective study was conducted, which included 45 SHI patients with tracheostomy from two hospitals. The GOSE instrument had been utilised in determining the impact of early tracheostomy on their functional outcome. Findings: Forty-five participants had completed the study and were included in the analysis. The univariate analysis performed for the three months post-discharge showed no significant association between the early tracheostomy and the functional outcome. However, the repeated analysis performed at six months post-discharge shows a significant association between these two variables (p=<0.001). The multivariate analysis demonstrated a consistent significant association between the early tracheostomy and the functional outcomes (p=<0.001). Conclusion: At six months post-discharge, the initiation of early tracheostomy contributes to a better functional outcome among patients with a SHI. The patients with early tracheostomy were 18.9% more likely to recover well than those with a late tracheostomy. The ability to assess the patient’s functional outcome using validated instruments such as GOSE should not only be limited to the physician or the surgeon but must also be empowered among other healthcare practitioners such as nurses and physiotherapists as well as the patient’s caregiver.